A case of second primary lung cancer diagnosed by surgical resection at salvage setting - Sakata, Shozo (Int Cancer Conf J, 2018)
We report a case of metachronous second primary lung cancer; it was initially clinically favored as progression of primary disease and finally diagnosed as a second primary lung cancer by surgical resection at salvage setting. A 73-year-old man was diagnosed with stage IV lung adenocarcinoma at initial presentation. He underwent two lines of chemotherapy, and the tumors regressed dramatically. However, the residual lung mass shadow expanded after 22 months. We performed resection at salvage setting. The gene status and histological subtype were not identical with that of the primary tumor, suggesting this to be a second primary lung cancer.